Mesenchymal Stem Cells Attenuate Lipopolysaccharide-Induced Inflammatory Response in Human Uterine Smooth Muscle Cells - Arunmani Mani; John W. Hotra; Sean C. Blackwell; Laura Goetzl; Jerrie S. Refuerzo (Thieme Medical Publishers, Inc., 2020)
Objective The aim of this study was to determine if mesenchymal stem cells (MSCs) would suppress the inflammatory response in human uterine cells in an in vitro lipopolysaccharide (LPS)-based preterm birth (PTB) model. Study Design Cocultures of human uterine smooth muscle cells (HUtSMCs) and MSCs were exposed to 5 μg/mL LPS for 4 hours and further challenged with 1 μg/mL LPS for a subsequent 24 hours. Key elements of the parturition cascade regulated by toll-like receptors (TLRs) through activation of mitogen-activated protein kinases (MAPKs) were quantified in culture supernatant as biomarkers of MSC modulation. Results Coculture with MSCs significantly attenuated TLR-4, p-JNK, and p- extracellular signal-regulated kinase 1/2 (ERK1/2) protein levels compared with HUtSMCs monoculture (p = 0.05). In addition, coculture was associated with significant inhibition of proinflammatory cytokines interleukin (IL)-6 and IL-8 (p = 0.0001) and increased production of anti-inflammatory cytokines IL-10 and transforming growth factor (TGF)-β1 (p = 0.0001). Conclusion MSCs appear to play a role in significantly attenuating LPS-mediated inflammation via alteration of down-stream MAPKs. MSCs may represent a novel, cell-based therapy in women with increased risk of inflammatory-mediated preterm birth.